Asian Sand Dust Regulates IL-32 Production in Airway Epithelial Cells: Inhibitory Effect of Glucocorticoids. Issue 4 (July 2019) - Shin, Jae-Min; Kim, Hwee-Jin; Park, Joo-Hoo; Hwang, You Jin; Lee, Heung-Man
Purpose: Epidemiologic studies have reported that Asian sand dust (ASD) is associated with chronic inflammatory diseases of the respiratory system. Glucocorticoids (GCs) have potent anti-inflammatory properties. The aims of this study were to evaluate the effects of GCs on ASD-induced interleukin-32 (IL-32) expression and to identify the underlying signaling pathways in airway epithelial cells. Methods: A 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay was used to evaluate cytotoxicity in A549 and human primary nasal epithelial cells. Expression levels of IL-32 messenger RNA and protein were measured by Western blot, real-time polymerase chain reaction, ELISA, and immunofluorescence staining. Signaling pathways were analyzed using specific inhibitors of Akt, MAPK, or NF- κ B. The effects of GCs on the expression of ASD-induced IL-32 were confirmed with ex vivo organ cultures of the nasal interior turbinate. Results: ASD (0–400 ng/mL) had no significant cytotoxic effects in A549 cells and human primary nasal epithelial cells. Expression levels of IL-32 were dose-dependently upregulated by ASD treatment in A549 cells. ASD induced phosphorylation of Akt, MAPK, and NF-κB, whereas GCs and specific inhibitors of Akt, MAPK, and NF-κB downregulated these activations and the expression of IL-32. These findings were further confirmed in human primary nasal epithelial cells and ex vivo organ cultures of the nasal interior turbinate. Conclusions: GCs have an inhibitory effect on ASD-induced IL-32 expression via the Akt, MAPK, and NF- κ B signaling pathways in airway epithelial cells.